Pengembangan kuda pacu dengan motor listrik untuk meningkatkan keterampilan berputar pada atlet senam artistik pria junior. - Herlambang, Tubagus; Fatkhu Royana, Ibnu; Kresnapati, Pandu; Aji Setyawan, Danang (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2025)
Physical Education (PE) plays a vital role in developing students' physical, emotional, social, and cognitive abilities. However, many PE learning processes still rely on teacher-centered approaches that limit student engagement and fail to create meaningful learning experiences. As a result, learning outcomes often lack relevance and sustainability. This study investigates how the use of Lesson Study (LS) affects both instructor professionalism and student learning. With LS, teachers work together to plan, observe, and methodically reflect on the learning process. This study used a qualitative approach with a case study method. 10 primary school teachers from Palembang, Indonesia, who teach physical education, participated in this study. The research instrument used was the Formative Class Evaluation (FCE), which consists of nine questions and four components: results, motivation, learning, and cooperation. The data analysis using the FCE indicated a significant improvement in teaching quality after the implementation of LS. The average FCE scores before LS ranged from 2.66 to 2.85. After LS, the average scores increased to between 2.71 and 2.86. These results suggest that although the relationship is relatively weak, LS implementation significantly enhanced classroom learning quality as perceived by the students. The findings suggest that LS has a positive impact on improving classroom learning experiences. Although the correlation between LS and student learning improvements was moderate, the statistical significance of the results highlights its potential as an effective professional development tool for teachers. Future research could explore the long-term effects of LS on student performance and the sustainability of these improvements.